Donald Davidson's truth-theoretic semantics - LePore, Ernest, 1950-; Ludwig, Kirk, 1959- (Oxford : Clarendon, 2007)
The work of Donald Davidson transformed the study of meaning. The authors present a study of Davidson's program of truth-theoretic semantics for natural languages, giving an exposition and critical examination of its foundations and applications.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Davidson, Donald, -- 1917-2003.; Semantics (Philosophy); Language and logic